MUSICAL PEDAGOGICAL SKILLS OF A TEACHER OF MUSIC CULTURE. - Holiknazarov Khurshidzhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
in this article, The Musical pedagogical skills of the teacher of music culture and the use of active teaching methods in the educational process. Primary acquisition of knowledge, consolidation of knowledge vatakomilization, formation of skills are developed. Choosing teaching methods, analyzing the content of the educational material before the exam, it is important that from the methods of Fidelity, the creative thinking of the learners, their perceptual abilities, life experience, adaptability to real activities. Teaching informational-developmental methods are told about the use of methods by which students receive educational information in a ready-made form or a statement of the teacher: lecture, narration, explanation, conversation, independent work with a book.